Mixed-dimensional V2CTx/Ti3C2Tx composite interlayer to boost electrochemical performance of Li-S batteries - Zhang, Weiqi; Zhang, Wenchao; Yao, Jing; Lu, Huiqing; Zhang, Xitian; Wu, LiLi (Frontiers in Chemistry, 2022)
Abstract: A mixed-dimensional V2CTx/Ti3C2Tx composite interlayer was successfully prepared to tackle severe polysulfide (LiPS) shuttling and sluggish sulfur redox kinetics for high-performance lithium–sulfur batteries. In the unique nanoarchitecture, two-dimensional Ti3C2Tx nanosheets served as a stable skeleton with superb electronic conductivity, good mechanical strength, and high polysulfide adsorption, whereas one-dimensional V2CTx nanorods played a crucial role in chemisorbing LiPSs and catalyzing the conversion of LiPSs due to their high polarity and electrocatalysis. With the synergistic effect of V2CTx and Ti3C2Tx composite nanostructures, the cells with the mixed-dimensional V2CTx/Ti3C2Tx composite interlayer showed an impressive long-term cycling stability and small capacity decay rate of 0.062% per cycle over 600 cycles at 1 C and exhibited an outstanding rate capability of 935.3 mAh·g−1 at 2 C.